Pengaruh Model Learning Cycle 7E Berbantuan LKS Terhadap Peningkatan Hasil Belajar Siswa Pada Konsep Hukum Newton Tentang Gerak di SMA Negeri 1 Sambuara - Lesti Bambulu; Theresje Mandang; Jimmy Lolowang (Charm Sains: Jurnal Pendidikan Fisika, 2022)
This study aims to determine the learning outcomes of students who use the Leaning Cycle 7e model assisted by LKS and also see student learning outcomes using conventional models on the physics subjects of Newton's legal material about motion in SMA Negeri 1 Sambuara. This research is a semi experimental study (quasi experiment) with Randomized Pretest-Posttest Control Group Design. The results showed that students who learned using the Leaning Cycle 7e model assisted by LKS, the average value of learning outcomes was 83.5, while students who learned using the conventional learning model the average value was 77. From these results it can be concluded that the use of the Learning Cycle model 7E assisted LKS is more influential on student learning outcomes than using conventional learning.